Imam Al-Sanusi’s Legacy in Islamic Education: Integrating Logic and Theology in Ahlussunnah wa al-Jamaah - M. Ubaidillah Luai Addimsiki; Duski Ibrahim; Muhammad Adil (AL-ISHLAH: Jurnal Pendidikan, 2025)
Imam al-Sanusi, a distinguished 9th-century AH theologian, is renowned for his synthesis of Islamic theology (Kalam) and logic (Mantiq), a methodology that profoundly influenced subsequent theological discourse. This study investigates the integration of logical principles in his seminal work Umm al-Barahin, addressing a scholarly gap in understanding the systematic role of logic in traditional Islamic theology. Using qualitative textual analysis, the research examines Umm al-Barahin to identify key theological constructs and their grounding in logical reasoning. Primary sources, including commentaries by later scholars such as al-Bajuri, are analyzed alongside historical and intellectual contexts that shaped al-Sanusi's thought. The findings reveal that Umm al-Barahin not only systematized Ash‘ari theology but also became a foundational text for the Ahlussunnah wa al-Jamaah, especially in the Malay world. The study underscores al-Sanusi's influence on subsequent generations of scholars and his enduring legacy in shaping Kalam as a rational discipline. The discussion highlights the pedagogical implications of al-Sanusi’s methodology, proposing ways his integration of logic and theology can enhance contemporary Islamic education. It argues for incorporating his structured approach into Aqeedah and Mantiq curricula within religious institutions to improve analytical engagement with Islamic doctrines. This research contributes to the ongoing discourse on Islamic pedagogy by emphasizing the relevance of classical theological methods in modern educational settings and reaffirming Imam al-Sanusi’s role in the intellectual history of Islamic thought.